2017
DOI: 10.1186/s12711-017-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential of shifting recombination hotspots to increase genetic gain in livestock breeding

Abstract: BackgroundThis study uses simulation to explore and quantify the potential effect of shifting recombination hotspots on genetic gain in livestock breeding programs.MethodsWe simulated three scenarios that differed in the locations of quantitative trait nucleotides (QTN) and recombination hotspots in the genome. In scenario 1, QTN were randomly distributed along the chromosomes and recombination was restricted to occur within specific genomic regions (i.e. recombination hotspots). In the other two scenarios, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…; Gonen et al. ), and several features of the genomic landscape (Begun and Aquadro ; Charlesworth et al. ; Duret and Arndt ).…”
Section: List Of 32 Genes Surveyed Organized By Step In the Recombinmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gonen et al. ), and several features of the genomic landscape (Begun and Aquadro ; Charlesworth et al. ; Duret and Arndt ).…”
Section: List Of 32 Genes Surveyed Organized By Step In the Recombinmentioning
confidence: 99%
“…Meiotic recombination, the reciprocal exchange of DNA between homologous chromosomes, during meiosis is a major determinant of genetic diversity in populations, influencing the fate of new mutations (Hill and Robertson 1966), the efficacy of selection (Felsenstein 1974;Charlesworth et al 1993;Comeron et al 1999;Gonen et al 2017), and several features of the genomic landscape (Begun and Aquadro 1992;Charlesworth et al 1994;Duret and Arndt 2008). Recombination is also required for successful gametogenesis in most species that reproduce sexually (Hassold and Hunt 2001).…”
mentioning
confidence: 99%
“…We may speculate that the correspondence between recombination rate and breed's age appears to reflect a correspondence between recombination rate and genetic heterogeneity because genetic heterogeneity within each breed tends to decrease with time due to inbreeding and artificial selection (Lipinski et al, 2008;Gibbs et al, 2009). This hypothesis is consistent with the assumption that benefits of recombination (generation of new allele combinations) prevail over its costs (occurrence of deleterious mutations) as long as the population remains sufficiently heterogeneous (Kim and Stephan, 2000;Nachman, 2001;Ohta, 1999).…”
Section: Discussionmentioning
confidence: 55%
“…Recombination makes a substantial contribution to genetic and phenotypic variability. Therefore, the efficiency of natural and artificial selection is critically dependent on the recombination rate (Battagin et al, 2016;Gonen et al, 2017). It has been shown that populations with higher recombination rate demonstrate a stronger response to selection (Gorlov et al, 1992;Korol and Iliadi, 1994;Otto and Barton, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation